A novel perspective of associativity of upper limb motor impairment and cortical excitability in sub-acute and chronic stroke - Saini, Megha; Singh, Neha; Kumar, Nand; Srivastava, M. V. Padma; Mehndiratta, Amit (Frontiers in Neuroscience, 2022)
BACKGROUND: The global inclination of stroke onset in earlier years of life and increased lifespan, 26 has resulted in an increased chronic post-stroke-related disability. The precise and simplistic approach 27 such as the correlation of Fugl-Meyer Assessment (FMA) with Transcranial Magnetic Stimulation 28 (TMS) parameters-Resting Motor Threshold (RMT) and Motor Evoked Potential (MEP) in patients 29 with stroke might play a critical role, given the prognostic value of MEP, a measure of cortical 30 excitability, and might be the key point in prescribing appropriate therapeutic strategies. 31 OBJECTIVE: The study aimed to determine the correlation of FMA-based impairment in the upper 32 extremity function specifically of the wrist and hand with respect to the neurophysiological parameters 33 of corticospinal tract integrity. 34 METHODS: The Institutional Review Board approved the study and sixty-seven (n=67) patients with 35 stroke were enrolled from the Department of Neurology, AIIMS. The motor assessment was performed 36 on patients by the upper extremity subset of Fugl-Meyer Assessment (FMA) and clinical history was 37 obtained. RMT and MEP of Extensor Digitorum Communis (EDC) muscle were measured via TMS. 38 RESULTS: A significant positive correlation was observed between Fugl-Meyer Assessment 39 Wrist/Hand (FMA W/H) and MEP scores (r=0.560, <0.001). Also, Fugl-Meyer Assessment Upper 40 Extremity (FMA UE) scores demonstrated a moderate positive association with MEP responsiveness 41 (r=0.421, <0.001). 42 CONCLUSION: MEP of the EDC muscle was found to be associated with sensorimotor control as 43 measured by FMA. Moreover, FMA W/H score values might be a better prognostic indicator of EDC 44 MEP responsiveness. Interestingly, a novel element comprising of the range of FMA UE and FMA 45 W/H components was observed to be a potential indicator of the MEP responsiveness and could also 46 indicate establishing FMA as a surrogate for TMS in resource-limited settings.